If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = 10v + -1(4v + 1) Reorder the terms: 3 = 10v + -1(1 + 4v) 3 = 10v + (1 * -1 + 4v * -1) 3 = 10v + (-1 + -4v) Reorder the terms: 3 = -1 + 10v + -4v Combine like terms: 10v + -4v = 6v 3 = -1 + 6v Solving 3 = -1 + 6v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-6v' to each side of the equation. 3 + -6v = -1 + 6v + -6v Combine like terms: 6v + -6v = 0 3 + -6v = -1 + 0 3 + -6v = -1 Add '-3' to each side of the equation. 3 + -3 + -6v = -1 + -3 Combine like terms: 3 + -3 = 0 0 + -6v = -1 + -3 -6v = -1 + -3 Combine like terms: -1 + -3 = -4 -6v = -4 Divide each side by '-6'. v = 0.6666666667 Simplifying v = 0.6666666667
| 75-3x=2x+15 | | 9+x=16 | | -1=-(3-8k)-k | | -8=-7m-(-3m+2) | | 6a-3(6-4a)=-6 | | 5x+78=11x+12 | | 65t=390 | | y-8=605 | | c-4=5 | | 18=b+9 | | 3(8n+2)+2=2-9n | | 5m-(-45k)+10m-10k= | | x+68=110 | | 3x^2-2=5x | | -5(-9a+3)=-4(-5-8a) | | n-5(n-3)=-n+6 | | -7-3x=3(3x+6) | | 12c^2+11c-15=0 | | 6x^2+13x-35=0 | | 12x^2+13x-35=0 | | 7-3m-6m=-20 | | 13-10x=46-31x | | 2p^2+5p-8=0 | | 3x+9=-51-7x | | -10z=.667 | | -11-4=-2.250t | | .583k=1 | | 113-6x=2x+17 | | -5n=25 | | -.600=-.700x | | 9x+4=7x+8 | | 4x^2+4x-8=1 |